A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species - van Tassell, James L.; Baldwin, Carole C. (Zootaxa, 2004)
Akko was originally described for a highly autapomorphic species of goby, A. dionaea, taken off Brazil. The genus is here recorded for the first time from the eastern Pacific Ocean. The poorly known eastern Pacific goby Amblyopus brevis G nther is redescribed as Akko brevis based on the study of numerous specimens recently collected off Panama and El Salvador, and Akko rossi is described as new from the coast of El Salvador. Akko dionaea has 11+16 vertebrae, 76 scales in the lateral series, non-overlapping scales on the caudal peduncle, and no melanophores on the pectoral fin or female genital papilla; A. brevis has 11+16 vertebrae, 53 60 scales in the lateral series, overlapping scales on the caudal peduncle, and no melanophores on the pectoral fin or female genital papilla; A. rossi has 11+17 vertebrae, 115 scales in the lateral series, overlapping scales on the caudal peduncle, and dense melanophores on the pectoral fin and female genital papilla.